P591 Anti-TNF therapy for Ulcerative Colitis in Brazil: a comparative real-world national multicentric study from the Brazilian Study Group of IBD (GEDIIB). (27th May 2021) - Sassaki, L Y; Magro, D O; Saad-Hossne, R; Baima, J P; Flores, C; Correia, L P D M P; Ferrari, M D L D A; Zacharias, P; Feitosa, M R; Santos, C H M; Lins Neto, M A D F; Quaresma, A B; et al.
Abstract: Background: Anti-TNF therapy represented a landmark in medical treatment of ulcerative colitis (UC). There is lack of data on the efficacy and safety of these agents in Brazilian patients, as public reimbursement is relatively recent. The present study aimed to analyze rates of clinical and endoscopic remission comparatively, between adalimumab (ADA) and infliximab (IFX), in Brazilian UC patients, and evaluate possible factors associated with remission after 1 year of treatment. Methods: A national retrospective multicenter study (24 centers) was carried out including patients with moderate-to-severe UC treated with anti-TNF therapy. Disease activity was categorized using Mayo score at baseline, weeks 8, 26 and 52. Clinical remission was defined as a partial Mayo score ≤ 2. Endoscopic remission was defined as a Mayo endoscopic subscore ≤ 1. Patients were allocated in 2 groups (ADA and IFX) and a comparative efficacy study was performed. Statistical analysis: logistic regression model was used to study effects of predictor variables on categorical outcomes, such as presence or absence of remission at week 52. Statistical significance was assumed if p <0.05. Results: Overall, 393 patients were included (111 ADA and 282 IFX). The mean age was 41.86 ± 13.60 y, 61.58% women, most patients had extensive colitis (62.40%) and 19.39% previous exposure to biological agent. Overall, clinical remission rate was 66.78%, 71.62% and 82.82% at weeks 8, 26 and 52, respectively. Remission rates were higher in the IFX group at weeks 26 (75.12% vs. 62.65 %, p <0.0001) and 52 (65.24% vs. 51.35%, p <0.0001) – figure 1. Overall, endoscopic remission was observed in 50% of patients at week 26 and in 65.98% at week 52, with no difference between the two groups (p = 0.114). Colectomy was performed in 23 patients (5.99%). The variables associated with clinical remission after 1 year of treatment were age, non-prior exposure to biological therapy, use of IFX, endoscopic remission at week 26 and no need for optimization (table 1). The variables associated with endoscopic remission after 1 year were non-prior exposure to biological therapy, clinical and endoscopic remission at week 26 and no need for optimization. Conclusion: In this national multicentric study, overall efficacy of anti-TNF therapy was similar to real world data with IFX and ADA. IFX treatment was associated with higher rates of clinical remission after 1 year in comparison to ADA. Patients naive to biological therapy presented higher rates of clinical and endoscopic remission. This is the first real world national study analyzing efficacy of anti-TNF agents in UC in Brazil.